Conflicts and expropriation of traditional territories in the Brazilian Amazon - Costa, Solange Maria Gayoso da; Hazeu, Marcel Theodoor; Costa , Larissa Marinho da (Argumentum, 2024)
This article analyses the conflicts and expropriation processes in the Amazon region. It highlights the resistance strategies implemented by local peoples to counter the appropriation and dispossession of their assets and way of life. The methodology employed was a systematic literature review, and a review of audiovisual materials that presented reports from leaders of social movements and traditional communities, these were identified and classified as: strengthening of identity; mobilisations, political organisation/links; and; use of counter-information. The use of counter-information, which emerged as an identified process of r-existence, was ultimately the basis for the analysis, which reflects on the conflicts and the processes of expropriation experienced in the Amazon region.
Keywords: Conflicts; Traditional People; R-existence; Amazon